2006
DOI: 10.1179/174329306x94318
|View full text |Cite
|
Sign up to set email alerts
|

Microcracking in multipass weld metal of alloy 690 Part 3 – Prevention of microcracking in reheated weld metal by addition of La to filler metal

Abstract: The effect of addition of La to a filler metal on microcracking (ductility dip cracking) in the multipass weld metal of alloy 690 was investigated with the aim of improving its microcracking susceptibility. The susceptibility to ductility dip cracking in the reheated weld metal could be greatly improved by adding 0 . 01-0 . 02 wt-%La to the weld metal. Conversely, excessive La addition to the weld metal led to liquation and solidification cracking in the weld metal. Hot ductility of the weld metal at the crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Researchers have proposed a variety of mechanisms of DDC, including impurity elements embrittlement, such as the segregation of S, P and other impurity elements at GBs, causing the loss of GBs ductility, thereby leading to DDC [17][18][19][20] , GB sliding [14,[21][22][23][24][25] , and precipitation-induced cracking (PIC), such as M 23 C 6 PIC [49] . In essence, DDC is caused by GB embrittlement [49] , and elements segregation at GBs and precipitates along GBs would affect GB embrittlement and DDC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have proposed a variety of mechanisms of DDC, including impurity elements embrittlement, such as the segregation of S, P and other impurity elements at GBs, causing the loss of GBs ductility, thereby leading to DDC [17][18][19][20] , GB sliding [14,[21][22][23][24][25] , and precipitation-induced cracking (PIC), such as M 23 C 6 PIC [49] . In essence, DDC is caused by GB embrittlement [49] , and elements segregation at GBs and precipitates along GBs would affect GB embrittlement and DDC.…”
Section: Discussionmentioning
confidence: 99%
“…Filler metal composition, such as S, P, H, C, Ti, Ta, Mo, La, Ce, and Nb, has a strong effect on DDC formation in austenitic weldments. Segregation of S, P, and H to GBs is a dominant factor for DDC aggravation in Ni-base alloys, whereas Ti, Ta, Mo, La, Ce, and Nb addition to a filler metal reduces the sensitivity of DDC [13,17,20,[27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] However, in the case of heat resistant cast steels, the low ductility is intrinsically due to their characteristic microstructure, resulting from both the manufacturing process and their composition. These materials are prepared by the sand casting technique and are stabilised using an aging treatment of several hours at y950uC.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have been reported that the primary cause of microcracking (ductility dip cracking) in alloy 690 was the reduction of hot ductility during cooling from welding attributed to the grain boundary segregation of impurity elements such as P and S. 8,9 Furthermore, the authors have also proposed an effective method for preventing microcracks in alloy 690 welds with using La added filler metals of alloy 690, and confirmed that microcracks in the multipass welds of alloy 690 could be completely prevented by using the filler metal added 0?01 mass%La. 10 Similar benefit to the hot cracking susceptibility by rare earth matel (REM) addition (0?02-0?04 mass-%) to the filler metal has been suggested in the Varestraint test of the alloy 690 weld metal. 11 On the other hand, type 316L stainless steel has been widely applied for pressurised water nuclear reactor components.…”
Section: Introductionmentioning
confidence: 93%